Information and communication technologies of the “Smart City” in the system of identification: forensic aspect - Doszhanova, A.B.; Begaliyev, Ye.N. (Bulletin of the Karaganda University “Law Series”, 2025)
This article examines the application of information and communication technologies (ICT) in forensic practice within the framework of the Smart City concept. Particular attention is paid to the use of intelligent video surveillance systems, machine learning algorithms, cloud computing, and biometric technologies to enhance the accuracy of personal identification and improve the responsiveness of law enforcement agencies. The integration of automated facial recognition systems with state and private sector databases is analyzed, along with their development prospects in light of regulatory and technical considerations. The study explores forensic aspects of ICT implementation in personal identification processes, including the application of artificial intelligence (AI) and big data analytics for identifying wanted individuals, preventing crimes, and increasing the transparency of law enforcement operations. Statistical data are presented to demonstrate the effectiveness of digital technologies in crime detection and public safety enhancement. Additionally, modern video surveillance systems and their functional capabilities in forensic identification are described. The relevance of further modernization and standardization of digital platforms for personal identification, their integration with national databases, and the improvement of personal data protection mechanisms has been substantiated. The prospects for establishing a unified national AI-based video surveillance system are considered, aiming to improve response efficiency, reduce identification errors, and enhance forensic analysis methodologies.